Effect of Organic Amendments on the Evolution of Soil Organic Matter in Soils Stressed by Intensive Agricultural Practices - Scotti, Riccardo; Conte, Pellegrino; Berns, Anne E.; Alonzo, Giuseppe; Rao, Maria A. (Current Organic Chemistry, 2013)
Losses of soil organic carbon often occur because of intensive agricultural practices that lead to removal of organic carbon following harvest production and to insufficient inputs. Organic amendments can be very appropriate for enhancing organic carbon content in very stressed agricultural soils. By enhancing soil organic matter, they generally play an important role in environmental matrices due to their capacity in retaining water and in enhancing nutrient availability to plants. Therefore, understanding the mechanisms by which organic amendments interact with other chemicals in the environment is of paramount importance. The attention was focused on farms near Sele river (Campania region, Italy), an area characterized by intensive agriculture. Two farms, with contrasting geopedologic properties (clay vs. sandy), were selected in order to study the effect of different doses of organic amendments containing compost from municipal solid wastes and wood-wastes (scraps of poplars pruning) at different ratios. The organic fractions were extracted from soil, after one and twelve months from amendment, and were analysed in order to establish their elemental composition and properties by FTIR, CPMAS 13C NMR spectroscopy and FFC-NMR relaxometry. Results showed an important role of soil geopedologic characteristics and experimental time in the evolution of humic acids. In less aerobic conditions as occurs in clay soils, organic matter was more stable, rich in carbonyl groups belonging to aldehydes and ketones, whereas under more aerobic conditions, occurring in sandy soils, organic matter had undergone a faster degradation, due to oxidative conditions and more intensive microbial activity.
Keywords: Humic acids